A model of discrete zero-sum two-person matrix games with grey numbers to solve dispute resolution problems in construction - Khanzadi, Mostafa; Turskis, Zenonas; Ghodrati Amiri, Gholamreza; Chalekaee, Alireza (Journal of Civil Engineering and Management, 2017)
Conflict between parties is a common issue in construction projects. In the present article, the conflicts be-tween contractor and employer in delayed Design-Bid-Build projects have been studied. Defining a case study, a dispute resolution method has been proposed. This case has been considered as a MCDM problem. This problem has been as-sumed as a discrete zero-sum two-person matrix game with grey numbers. Among the four alternatives available for con-tractor and employer in the proposed case study, termination is the last alternative that decision makers choose. Based on different risk values, authors determined the optimal solution for both parties. This article integrates some linguistic criteria together with time and cost, providing the better conditions to avoid lengthy bargaining.